Ergonomic Study of Reading Room Facilities and Infrastructure Faculty of Social and Political Sciences, Bengkulu University - Gunaidi, Aang; Yoanda, Sely (UIN Raden Intan Lampung, 2023)
Ergonomics studies in the Reading Room of the Faculty of Social and Political Sciences, Bengkulu University need to be carried out so that users feel comfortable in the library. The aims of this research is to examine the application of ergonomics concepts to the facilities and infrastructure of the Reading Room, Faculty of Social and Political Sciences, Bengkulu University, which include bookshelves, reading tables, reading chairs, lighting, temperature and humidity. This research was conducted using quantitative research methods with a survey approach. Data collection techniques by distributing questionnaires to 183 respondents using the Ergonomic Function Deployment (EFD) method based on ergonomic aspects: effective, comfortable, safe, healthy, and efficient. The results showed that the respondents' assessment of the facilities and infrastructure of the FISIP UNIB Reading Room was as follows (1) bookshelf 82% (good); (2) reading table 72.6% (good); (3) reading chair 70.8% (good); (4) lighting level of 58% (sufficient); (5) temperature and humidity 58% (enough). The conclusion in this study is that in the Reading Room of the Faculty of Social and Political Sciences, Bengkulu University, it is not optimal in applying the ergonomic concept. The Reading Room of the Faculty of Social and Political Sciences, University of Bengkulu needs to pay attention to the maximum application of ergonomics so that it can provide comfort for users visiting the library.